Escravidão negra em Belém: mercado, trabalho e liberdade (1810-1850) - PALHA, Bárbara da Fonseca (Universidade Federal do Pará, 2014)
Between the years 1810 and 1850, the presence of slave workers in Belém was significant. Demographically, this population accounted for almost half the population of the city, formed by the urban parishes of the Sé and Campina. This essay examine slavery in Belém, from the different aspects such as the salve trade, the geographic and ethnic origin of the slaves, the demographics and the colors of slave population, the slave market, mobility, freedom and social control, permeated by social, political and economic events in Brazil and the province of Grão-Pará during the fist-half of the nineteenth century, such as the arrival of the royal family and the opening of ports, independence, Cabanagem and promulgation of laws against trade slave in 1815, 1831 and 1850. Narratives of foreign travelers, the press, postmortem inventories, public records, legislation and liberty action are some of the sources used to build the scenery: the Belém of the first-half of the nineteenth century, and our actors: the slave workers.